2022
DOI: 10.1007/s10072-022-05997-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported impact of the COVID-19 pandemic and lockdown on young patients with tic disorders: findings from a case–control study

Abstract: Background Little is known about the perceived impact of the COVID-19 pandemic and subsequent lockdown measures on young patients with tic disorders. Previous studies focused on clinician and parent ratings of tic severity, whereas the only international self-report data are available for adult populations. We present the first findings from a case–control study on children and adolescents with tics during lockdown in Italy. Methods We surveyed 49 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“… [34] In particular, studies have shown that the pandemic had a negative impact on OCD symptom severity [22] , [35] and on tic symptom severity. [24] , [36] Similar to these studies, parents surveyed in our study reported that their children’s tics and OCD symptoms did increase in severity. Impact on OCD symptoms appeared to be universally negative, regardless of presence of co-occurring tics.…”
Section: Discussionsupporting
confidence: 84%
“… [34] In particular, studies have shown that the pandemic had a negative impact on OCD symptom severity [22] , [35] and on tic symptom severity. [24] , [36] Similar to these studies, parents surveyed in our study reported that their children’s tics and OCD symptoms did increase in severity. Impact on OCD symptoms appeared to be universally negative, regardless of presence of co-occurring tics.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, they need our reassurance and help in these difficult times, supported by a network of informed health-care professionals. Perceived changes in tic severity during the lockdown were also recently described in school-age patients with tic disorders ( 17 ). In addition, during the global pandemic caused by COVID-19, it was reported a dramatic increase in functional tic-like behaviors in vulnerable children and adolescents after social media exposure ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 72%
“…The authors included 49 children with tics and 245 matched controls who were asked to provide information about lockdown-related changes to daily activities. More than half of patients reported perceived changes in tic severity, restlessness and irritability during the pandemic ( Termine et al . 2022 ).…”
Section: Resultsmentioning
confidence: 99%